Multi-omics analysis reveals adipose-tumor crosstalk in patients with colorectal cancer - Holowatyj, Andreana N.; Haffa, Mariam; Lin, Tengda; Scherer, Dominique; Gigić, Biljana; Ose, Jennifer; Warby, Christy A.; Himbert, Caroline; Abbenhardt-Martin, Clare; Achaintre, David; Boehm, Juergen; Boucher, Kenneth M.; et al. (Cancer Prevention Research, 2020)
Obesity and obesity-driven cancer rates are continuing to rise worldwide. We hypothesize that adipocyte-colonocyte interactions are a key driver of obesity-associated cancers. To understand the clinical relevance of visceral adipose tissue in advancing tumor growth, we analyzed paired tumor-adjacent visceral adipose, normal mucosa, and colorectal tumor tissues as well as presurgery blood samples from patients with sporadic colorectal cancer. We report that high peroxisome proliferator-activated receptor gamma (PPARG) visceral adipose tissue expression is associated with glycoprotein VI (GPVI) signaling—the major signaling receptor for collagen—as well as fibrosis and adipogenesis pathway signaling in colorectal tumors. These associations were supported by correlations between PPARG visceral adipose tissue expression and circulating levels of plasma 4-hydroxyproline and serum intercellular adhesion molecule 1 (ICAM1), as well as gene set enrichment analysis and joint gene-metabolite pathway results integration that yielded significant enrichment of genes defining epithelial-to-mesenchymal transition—as in fibrosis and metastasis—and genes involved in glycolytic metabolism, confirmed this association. We also reveal that elevated prostaglandin-endoperoxide synthase 2 (PTGS2) colorectal tumor expression is associated with a fibrotic signature in adipose-tumor crosstalk via GPVI signaling and dendritic cell maturation in visceral adipose tissue. Systemic metabolite and biomarker profiling confirmed that high PTGS2 expression in colorectal tumors is significantly associated with higher concentrations of serum amyloid A and glycine, and lower concentrations of sphingomyelin, in patients with colorectal cancer. This multi-omics study suggests that adipose-tumor crosstalk in patients with colorectal cancer is a critical microenvironment interaction that could be therapeutically targeted. - See related spotlight by Colacino et al., p. 803
Gesehen am 13.11.2020